2017
DOI: 10.1093/femsec/fix120
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in an intensively managed landscape is structured by landscape connectivity

Abstract: Intensively managed land increases the rate of nutrient and particle transport within a basin, but the impact of these changes on microbial community assembly patterns at the basin scale is not yet understood. The objective of this study was to investigate how landscape connectivity and dispersal impacts microbial diversity in an agricultural-dominated watershed. We characterized soil, sediment and water microbial communities along the Upper Sangamon River basin in Illinois-a 3600 km2 watershed strongly influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Our study showed weaker connectivity between the terrestrial and aquatic environments than has been shown elsewhere (Crump et al ., ; Ruiz‐González et al ., ; Griffin et al ., ). Our sampling scale was sufficient to detect spatial changes in soil microbial communities (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our study showed weaker connectivity between the terrestrial and aquatic environments than has been shown elsewhere (Crump et al ., ; Ruiz‐González et al ., ; Griffin et al ., ). Our sampling scale was sufficient to detect spatial changes in soil microbial communities (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Our study provides new insights into the connectivity between bacterial communities in soil, stream water and stream sediments at small spatial scales (~1 m–1 km), building on previous knowledge obtained at much larger spatial scales (Crump et al ., ; Ruiz‐González et al ., ; Griffin et al ., ). Through intensive sampling of the soil, stream water and stream sediment in a native forest catchment, we have shown that, while the microbial communities in these different habitats are distinct from one another, there appears to be a degree of connectivity among them all, but the proportion of shared taxa varies by habitat combination.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations